THE ANALYSIS OF TECHNICAL EFFICIENCY OF PADDY PRODUCTION IN IADA KETARA: NEW TECHNOLOGY PACKAGE - Wan Roshidah Fadzim; Ruhaida Saidon; Roslina Kamaruddin (Journal of Islamic, Social, Economics and Development, 2023)
Rice, a fundamental staple crop not only in Malaysia but worldwide, has faced a challenge in Malaysia where the actual paddy production has lagged behind its potential. Recently, Universiti Putra Malaysia (UPM) introduced a technological package for paddy production called PadiU Putra, with the aim of enhancing both the quantity and quality of paddy output. Therefore, the objective of this study is to assess the impact of the PadiU Putra technology package on the technical efficiency of paddy production in IADA KETARA, Terengganu, Malaysia.To analyze the technical efficiency of paddy yield, an output-oriented Data Envelopment Analysis (DEA) approach was employed. This analysis was based on a cross-sectional survey and face-to-face interviews with 121 paddy farmers, who were selected using stratified random sampling in 2019. The study's results revealed that the implementation of the PadiU Putra technology package led to a notable 23 percent increase in the technical efficiency of paddy production when compared to non-PadiU Putra technology practices in the study area. Overall, these findings underscore the successful role of the PadiU Putra technology package in boosting paddy production within the study area.